Counselling by Primary Care Physicians May Help Patients with Heartburn-Predominant Uninvestigated Dyspepsia - Pierre Paré; Joanna Lee M Math; Ian A Hawes (Canadian Journal of Gastroenterology)
OBJECTIVE: To determine whether strategies to counsel and empower patients with heartburn-predominant dyspepsia could improve health-related quality of life.